Is the Glass Half Empty or Half Full? School Enrollment, Graduation, and Dropout Rates in Latin America - Marina Bassi; Matias Busso; Juan Sebastian Munoz (Inter-American Development Bank (IDB), 2013)
This paper uses 113 household surveys from 18 Latin American countries to document patterns in secondary school graduation rates over the period 1990 2010. It is found that enrollment and graduation rates increased dramatically during that period, while dropout rates decreased. Two explanations for these patterns are provided. First, countries implemented changes on the supply side to increase access, by increasing the resources allocated to education and designing policies to help students staying in school. At the same time, economic incentives to stay in school changed, since returns to secondary education increased over the 1990s. Despite this progress, graduation rates are low, and there persist remarkable gaps in educational outcomes in terms of gender, income quintiles, and regions within countries. In addition, wage returns have recently stagnated, and the quality of education in the region is low, casting doubts on whether the positive trend is sustainable in the medium term.
Keywords: 330